2006
DOI: 10.1111/j.1365-2958.2006.05344.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of two Entamoeba histolytica strains with different virulence phenotypes identifies peroxiredoxin as an important component of amoebic virulence

Abstract: SummaryEntamoeba histolytica is a protozoan intestinal parasite that causes amoebic colitis and amoebic liver abscess. To identify virulence factors of E. histolytica, we first defined the phenotypes of two E. histolytica strains, HM-1:IMSS, the prototype virulent strain, and E. histolytica Rahman, a strain that was reportedly less virulent than HM-1:IMSS. We found that compared with HM-1:IMSS, Rahman has a defect in erythrophagocytosis and the ability to cause amoebic colitis in human colonic xenografts. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
102
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 41 publications
4
102
2
Order By: Relevance
“…Since first described nearly 2 decades ago (21,28,57), LIM domain-containing proteins have been identified in a wide range of eukaryotes, including protozoa (16,30,45), plants (5,20,40), and yeast (Saccharomyces cerevisiae) (39), stressing the evolutionary importance of these proteins. In the parasitic protozoan Entamoeba histolytica, a few studies have revealed the presence of such proteins (17,36), although to date, no LIM domain-containing proteins have been characterized in this organism. The name LIM is derived from the three developmentally regulated transcription factors, LIN-11 of Caenorhabditis elegans (21), Isl1 of rat (28), and MEC-3 of C. elegans (57) in which the LIM domain was initially identified.…”
mentioning
confidence: 99%
“…Since first described nearly 2 decades ago (21,28,57), LIM domain-containing proteins have been identified in a wide range of eukaryotes, including protozoa (16,30,45), plants (5,20,40), and yeast (Saccharomyces cerevisiae) (39), stressing the evolutionary importance of these proteins. In the parasitic protozoan Entamoeba histolytica, a few studies have revealed the presence of such proteins (17,36), although to date, no LIM domain-containing proteins have been characterized in this organism. The name LIM is derived from the three developmentally regulated transcription factors, LIN-11 of Caenorhabditis elegans (21), Isl1 of rat (28), and MEC-3 of C. elegans (57) in which the LIM domain was initially identified.…”
mentioning
confidence: 99%
“…The authors hypothesized that the glycans may protect parasite adhesion molecules from proteolysis or that the proteophosphoglycans may regulate the ability of parasite surface molecules to interact with host cell receptors. Two genes with lower expression in E. histolytica Rahman have been genetically linked to virulence: overexpression of the peroxiredoxin gene in E. histolytica Rahman imparted increased resistance to oxidative stress (19), and antisense inhibition of the light lectin subunit in E. histolytica HM-1:IMSS resulted in decreased cytotoxicity and fewer amebic liver abscesses in hamsters (3).…”
mentioning
confidence: 99%
“…This strain, originally isolated from an asymptomatically infected person (21, 34) has long been described as having attenuated virulence (14). E. histolytica Rahman was recently shown to have decreased levels of cytotoxicity, decreased ability to phagocytose erythrocytes, decreased ability to elicit colitis in human colonic xenografts, and decreased resistance to oxidative stress (19). Interestingly, relatively few genetic differences were noted between E. histolytica HM-1:IMSS and E. histolytica Rahman based on comparative genomic hybridization analysis (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In areas where the infection is highly endemic, such as the Mirpur region of Dhaka, Bangladesh, over 50% of children may become infected by 5 years of age (3), yet only about 10% of all infections become symptomatic (4,5). Isolated strains of E. histolytica have been shown to have different levels of virulence both in vivo and in vitro (6)(7)(8), which may in part determine whether or not a particular infection becomes invasive.…”
mentioning
confidence: 99%